Psychological Practice with Women : Guidelines, Diversity, Empowerment - Enns, Carolyn Zerbe; Rice, Joy K.; Nutt, Roberta Lynn, 1944- (Psychology of women book series., 2015)
"Applying a feminist lens to current concerns facing individuals, families, schools, communities, and nations can provide deeper insight into and understanding of contemporary social issues, including poverty, immigration, violence toward and abuse of women and children, and physical and mental health disparities. Most important, such work can identify and promote interventions and solutions that improve women's status in society and advance social justice. The American Psychological Association's (APA's) Psychology of Women Book Series is designed to support and disseminate feminist scholarship on education, research, and practice that can contribute to advocacy and social activism on behalf of women and other disempowered groups. It reflects a primary principle of feminist psychology: the application of knowledge through action. Whereas consciousness of women's issues and the psychology of women began with emphasis primarily on White, middle-class women, the series extends scholarship and concerns about diversity and the intersectionality of multiple social identities of individuals, highlighting not only demographic trends in the United States but also the interplay between national and global concerns. The interacting identities considered include race, ethnicity, gender, sexual orientation, nationality, socioeconomic status, religion, ability, and age. Specific objectives are to synthesize, integrate, and apply empirical knowledge and clinical perspectives for women who represent dimensions of diversities previously ignored or underrepresented in research and clinical application and to extend psychological theory on women and gender so that it is both more diverse and inclusive of all groups of women. This book provides valuable examples of how aspirational guidelines can be applied to clinical practice and the provision of mental health services to women and girls. Its focus on the intersection and multiple layers of women's social identity is unique and should provide many insights for those interested in working with diverse groups. Each of the chapters that focus on a particular population includes extensive consideration of feminist scholarship (both research and theory) relevant to the group identity, applies the relevant scholarship, explores a variety of therapeutic approaches through the use of case studies, and considers possibilities for advocacy and social change. Moreover, the chapter authors highlight positive approaches based on resiliency and targeted toward the empowerment of women. The editors begin and end the book by emphasizing the theme of the transformation of psychology and the necessity of inclusion of essential feminist perspectives. They see the book as an effort to promote such a "transformation on how we understand, conceptualize and treat diverse groups of women" (p. 4). Transforming the knowledge, norms, and practices of a profession requires a great deal more than one book. Nonetheless, through the presentation of up-to-date culturally based research, current feminist theory, and their application to clinical practice, this book will help to advance and transform the practice of psychology"--Foreword. (PsycINFO Database Record (c) 2014 APA, all rights reserved).